Sjogren's Syndrome in the Mask of Hypokalemia: A Case Report - Krishna Bahadur Sodari; Pragyan Basnet; Krishna Adhikari (Journal of Nepal Medical Association)
Sjogren's syndrome is an autoimmune disease characterized by lymphocytic infiltration of exocrine glands resulting in xerostomia and dry eyes affecting entire body. A 40-year-old woman presented with generalized weakness and shortness of breath. She had reduced muscle power (2/5) with reduced tone, and absent reflexes in four limbs. Further investigation revealed severe hypokalemia with metabolic acidosis. She was treated with intravenous potassium chloride and diagnosed with Sjogren's syndrome based on her serology profile. After treatment, her condition improved. Hypokalemia occurs due to increased renal excretions of potassium. Distal Renal Tubular Acidosis is a major cause of potassium loss in urine. Sjogren's Syndrome is an important cause of Distal Renal Tubular Acidosis, which can present as severe hypokalemia. Although it commonly presents with symptoms like dry eyes and dry mouth, it can rarely present as Distal Renal Tubular Acidosis and hypokalemia as the primary presentation. Sjogren's syndrome should be suspected in patients with hypokalemia with features of Distal Renal Tubular Acidosis.